Dinheiro, valor e o valor do dinheiro em Marx: uma revisão da literatura recente - Ambrozio, Luiz Felipe Arruda (2013)
This work has the goal of to execute a review at the recent literature on the Marx s theory of money. For this, relevant works produced at last two decades by Brazilian and foreign authors were elected. Those works were divided at three major themes, who comprise the three chapters of this dissertation. The themes are: the relation between the Marx s theory of value and the concept of money; the problem brought to Marx s theory of money by the ending of dollar-gold standard, and, the determination of the value of the money. At the end of this work was made a critical review of the ideas exposed in which has sought to establish points of connection and dissent between the authors.